Design and characterization of visible-light LED sources for microstructured photoreactors. Issue 6 (16th October 2018) - Roibu, Anca; Morthala, Rishi Bharadwaj; Leblebici, M. Enis; Koziej, Dorota; Van Gerven, Tom; Kuhn, Simon
Abstract : Experimental and modeling toolbox to quantify the light uniformity, photon flux and energy efficiency of microstructured photoreactors. Abstract : The design of stable, compact, and uniform LED light sources for continuous microstructured photoreactors is reported. The electrical and thermal properties of green LEDs are translated into an efficient control and cooling strategy. To study the irradiance uniformity and efficiency to irradiate the microfluidic channel, narrow viewing angle LEDs were configured in four arrays. The irradiance uniformity experienced by the microchannel is determined with an irradiance model, which is improved by using near-field goniophotometer measurements for small distances between the light source and reactor. Maximum light uniformity is achieved below the LED-reactor distance of 1.5 cm. Exceeding this distance and employing arrays with a larger number of LEDs did not improve the uniformity on the microchannel. Furthermore, the energy efficiency of the photoreactor is quantified by combining near-field goniophotometer measurements, irradiance modeling and actinometry. It was shown that below 2 cm the photon losses were reduced when the LED positions matched the microchannel geometry, however a low utilization of the consumed electrical energy is observed irrespective of the LED array design. The characterization methodology presented in this study enables the identification and quantification of the limiting factors.